America's working women: A documentary history, 1600 to the present - Baxandall, (1939- ...)., Rosalyn Fraad; Gordon, Linda; Reverby, Susan (W.W. Norton, 1995)
A landmark work when it appeared in 1976, America's Working Women helped form the field of women's studies and transform labor history. Now the authors have enlarged the dimensions of this important anthology; more than half the selections and all the introductory material are new. Spanning the years from 1600 to the present, selections from diaries, popular magazines, historical works, oral histories, letters, songs, poetry, and fiction show women's creativity in supporting themselves, their families, and organizations or associations. Slave women recall their field work, family work, and sabotage. We see Indian women farming, and we also see the white culture coercing Indian women to give up farming. We see women in industry playing a central part in the union movement while facing the particular hazards of women's jobs and working conditions. New selections show the historical origins of today's important issues: sexual harassment, equal pay, "sex work," work in the underground economy, work in the home, and shift work. With an expanded focus on women from all racial and ethnic backgrounds and regions, America's Working Women grounds us in the battles women have fought and the ones they are in the process of winning.
Accessible en ligne : https://archive.org/details/isbn_9780393312621
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; discours dominant; droits des femmes*; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; racisme; racisme systémique; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail; travail des femmes*; états-unis

Unruly women: The politics of social and sexual control in the old South - Bynum, Victoria E. (University of North Carolina Press, 1992)
In this richly detailed and imaginatively researched study, Victoria Bynum investigates "unruly" women in central North Carolina before and during the Civil War. Analyzing the complex and interrelated impact of gender, race, class, and region on the lives of black and white women, she shows how their diverse experiences and behavior reflected and influenced the changing social order and political economy of the state and region. Her work expands our knowledge of black and white women by studying them outside the plantation setting.Bynum searched local and state court records, public documents, and manuscript collections to locate and document the lives of these otherwise ordinary, obscure women. Some appeared in court as abused, sometimes abusive, wives, as victims and sometimes perpetrators of violent assaults, or as participants in illicit, interracial relationships. During the Civil War, women frequently were cited for theft, trespassing, or rioting, usually in an effort to gain goods made scarce by war. Some women were charged with harboring evaders or deserters of the Confederacy, an act that reflected their conviction that the Confederacy was destroying them.These politically powerless unruly women threatened to disrupt the underlying social structure of the Old South, which depended upon the services and cooperation of all women. Bynum examines the effects of women's social and sexual behavior on the dominant society and shows the ways in which power flowed between the private and public spheres. Whether wives or unmarried, enslaved or free, women were active agents of the society's ordering and dissolution.
Disponible en livre numérique et en format imprimé.
Keywords: 1800-1899; amériques; approches et analyses; civil war; cours; discipline; féminisme matérialiste; his4443; histoire; histoire des femmes*; histoire et politique; intersectionnalité; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

In joy and in sorrow: Women, family, and marriage in the Victorian South, 1830-1900 - Bleser, Carol (Oxford Univ. Press, 1991)
In Joy and in Sorrow brings together some of the finest historians of the South in a sweeping exploration of the meaning of the family in this troubled region. In their vast canvas of the Victorian South, the authors explore the private lives of Senators, wealthy planters, and the belles of high society, along with the humblest slaves and sharecroppers, both white and black. Stretching from the height of the antebellum South's pride and power through the chaos of the Civil War and Reconstruction to the end of the century, these essays uncover hidden worlds of the Southern family, worlds of love and duty–and of incest, miscegenation, and insanity. Featuring an introduction by C. Vann Woodward, Pulitzer Prize-winning author of Mary Chesnut's Civil War, and a foreword by Anne Firor Scott, author of The Southern Lady, this work presents an outstanding array of historians: Eugene Genovese, Catherine Clinton, Elizabeth Fox-Genovese, Carol Bleser, Drew Faust, James Roark, Michael Johnson, Brenda Stevenson, Bertram Wyatt-Brown, Jacqueline Jones, Peter Bardaglio, and more. They probe the many facets of Southern domestic life, from the impact of the Civil War on a prominent Southern marriage to the struggles of postwar sharecropper families. One author turns the pages of nineteenth century cookbooks, exploring what they tell us about home life, housekeeping, and entertaining without slaves after the Civil War. Other essays portray the relationship between a Victorian father and his devoted son, as well as the private writings of a long-suffering Southern wife. In Joy and in Sorrow offers a fascinating look into the tangled reality of Southern life before, during, and after the Civil War. With this collection of essays, editor Carol Bleser provides a powerful new way of understanding this most self-consciously distinct region. In Joy and in Sorrow will appeal to everyone interested in marriage and the family, the problems of gender and slavery, as well as in the history of the South, old and new.
Papers of the "Forth Hill Conference on Southern Culture", held at Clemson Univ. (1989). Textes de Fort Hill Conference on Southern Culture, tenue à Clemson University au printemps de 1989.
Keywords: 1800-1899; Noires américaines; amériques; approches et analyses; conditions des femmes*; cours; discipline; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; mariage; patriarcat; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; états-unis; états-unis (sud)

Peau noire, masques blancs - Fanon, Frantz (Seuil, 1971)
La décolonisation faite, cet essai de compréhension du rapport Noir-Blanc a gardé toute sa valeur prophétique : car le racisme, malgré les horreurs dont il a affligé le monde, reste un problème d'avenir. Il est ici abordé et combattu de front, avec toutes les ressources des sciences de l'homme et avec la passion de celui qui allait devenir un maître à penser pour beaucoup d'intellectuels du tiers monde.
Première publication: 1952
Keywords: 1900-1999; 1950-1959; amériques; antilles; approches et analyses; colonialisme; cours; discipline; décolonialisme; europe; fem1000; femmes* noires; france; féminisme décolonial; har4600; histoire; postcolonialisme; premier cycle; psychanalyse; périodes historiques; racisme; régions géographiques; sciences; sciences humaines; systèmes d'oppressions